Determinação simultânea de paracetamol e cafeína em formulações farmacêuticas usando análise por injeção em fluxo com detecção amperométrica - Silva, Wesley Cadena da (2011)
This work reports the development of a quick and easy method for simultaneous determination of paracetamol (PA) and caffeine (CA) in pharmaceutical formulations using Flow Injection Analysis with Multiple Pulse Amperometric detection (FIA-MPA). A singleline flow injection system was employed using a home-made electrochemical wall-jet cell in the three electrode configuration. Boron-doped diamond electrode (BDD; ~8000 ppm) was used as the working electrode. The strategy used in the simultaneous determination of PA and CA by FIA-MPA was the application of three sequential and cyclic potential pulses in function of the time: (1) +1.20 V/50ms: oxidation of PA and selective quantification of PA; (2) +1.55 V/50ms: oxidation of both analytes (CA e PA) and quantification of CA through the subtraction of the current signal detected at + 1.20 V. However the current detected at +1.20 V should be multiplied for a correction factor; (3) +0.40V/100ms: potential pulse applied in order to avoid contamination of BDD working electrode (probably due to the adsorption of PA or CA or oxidations products). The PA oxidation current detected at +1.20 V is greater than the PA current detected at +1.55 V, a simple subtraction between currents detected at the two potential pulses does not directly yield the CA oxidation current. To circumvent this problem, we applied a correction factor (fator = iPA+1,55 V/iPA+1,2 V) that corresponds to the exact difference between the current detected for PA at +1.20 V and +1.55 V. Then, the current originating from CA oxidation detected at +1.55 V can be calculated using the following equation: [iCA = i+1,55 V (fator x i+1,20 V)]. Besides this, several parameters of the FIA-MPA system were studied and/or optimized: potential pulses times, current sampling in each transient signal, flow rate and injection volume. Both compounds displayed good linearity over a large concentration range (1.0 755 mg L-1 for PA and 1.0 315 mg L-1 for CA), with excellent correlation coefficients for both analytes (R = 0.999). The correction factor is constant over a large PA concentration range (9.9-177.0 mg L-1; correction factor = 0.771 ± 0.012; n = 13). The proposed method was used for the determination of PA and CA in pharmaceutical formulations and the obtained results were similar to those obtained by HPLC. Recovery studies were also carried out (~ 100 %).